Investigating the Visual Fatigue in VDT Operators in the Banks of Qasr-e Shirin (Kermanshah-Iran). - Darsanj, Afshin; Yarmohammadi, Hamed; Poursadeghiyan, Mohsen; Dalvand, Sahar; Javadzad, Hossein; Salehi, Razie; Gharagozlou, Faramarz (Archives of Hygiene Sciences)
Background & Aims of the Study: Considering the increasing use of computers in the official and social environments of Iran, it seems in the near future, eye and physical discomfort caused by working with computers will become one of the most important health issues in our society, which seriously threatens the employee health and, as a result, leads to significant financial and industrial losses. The aim of this study is determination of the visual fatigue of video display terminal (VDT) operators in the banks of Qasr-e Shirin, Kermanshah province of Iran. Materials and Methods: This study was carried out, using a descriptive-analytical method on all 58 VDT operators of Qasar-e shirin banks in 2017. A two-part questionnaire including demographic information and visual fatigue was used to measure visual fatigue. Data were analyzed by descriptive statistics (frequency, percentage, central indices and dispersion) as well as independent t-test, Mann-Whitney, ANOVA and Pearson correlation tests, using SPSS Ver. 16. Results: The results showed the mean and standard deviation of visual fatigue was 48.76±28.18. Visual fatigue was not observed in 8.6% of subjects, but 24.1% had low, 24.1% had moderate and 43.1% had severe visual fatigue. The highest visual fatigue (3.49±1.93) was found in subjects with glasses and the lowest (3.35±2.43) was seen in single individuals. There were positive and significant relationships among working hours with visual strain and visual fatigue subscale; also, between the number of working hours with visual strain and visual fatigue subscale. Conclusion: The findings suggest the high level of visual fatigue. Therefore, it is recommended to avoid visual fatigue by corrective and preventive measures such as reducing the working time with VDTs and/or using standard computers.